GABAB Receptors Expressed in Human Aortic Endothelial Cells Mediate Intracellular Calcium Concentration Regulation and Endothelial Nitric Oxide Synthase Translocation. (9th July 2014) - Wang, Xu-Ping; Cheng, Zhen-Ying; Schmid, Katrina L.
Abstract : GABAB receptors regulate the intracellular Ca 2+ concentration ([Ca 2+ ] i ) in a number of cells (e.g., retina, airway epithelium and smooth muscle), but whether they are expressed in vascular endothelial cells and similarly regulate the [Ca 2+ ] i is not known. The purpose of this study was to investigate the expression of GABAB receptors, a subclass of receptors to the inhibitory neurotransmitter γ -aminobutyric acid (GABA), in cultured human aortic endothelial cells (HAECs), and to explore if altering receptor activation modified [Ca 2+ ] i and endothelial nitric oxide synthase (eNOS) translocation. Real-time PCR, western blots and immunofluorescence were used to determine the expression of GABAB1 and GABAB2 in cultured HAECs. The effects of GABAB receptors on [Ca 2+ ] i in cultured HAECs were demonstrated using fluo-3. The influence of GABAB receptors on eNOS translocation was assessed by immunocytochemistry. Both GABAB1 and GABAB2 mRNA and protein were expressed in cultured HAECs, and the GABAB1 and GABAB2 proteins were colocated in the cell membrane and cytoplasm. One hundred μ M baclofen caused a transient increase of [Ca 2+ ] i and eNOS translocation in cultured HAECs, and the effects were attenuated by pretreatment with the selective GABAB receptor antagonists CGP46381 and CGP55845. GABAB receptors are expressed in HAECs and regulate the [Ca 2+ ] i and eNOS translocation. Cultures of HAECs may be a useful in vitro model for the study of GABAB receptors and vascular biology.